Essence and Determinants of Personal Crisis: Theoretical Interdisciplinary Analysis Attempt (Social-Psychological View) - Nagorny, A. I. (Psychological Prospects Journal, 2012)
The article reveals the interdisciplinary approach, from the positions of psychology and sociology, as a crucial point to considering the essence, determination and solving the phenomenon of personality crisis.